Convective drying of yacón (Smallanthus sonchifolius) slices: A simple physical model including shrinkage. (1st April 2022) - Marques, Bianca Cristine; Plana-Fattori, Artemio; Flick, Denis; Tadini, Carmen Cecilia
Abstract: Yacón is a tuberous root from the Andean region, and a functional food due to the presence of fructo-oligosaccharides (FOS). Due to its high moisture in natura, the product is prone to microbial degradation. The evolution of yacón cylindrical slices under convective drying is here studied from experimental work and theoretical considerations about bulk properties. The operation of a pilot-scale convective dryer allowed monitoring the moisture and dimensions of yacón slices. Evolution of moisture under controlled temperature and relative humidity conditions is described through a two-parameter drying kinetics model. A novel approach for estimating shrinkage effects is proposed, comparing measured dimensions with predictions based upon hypothetical shrinkage behaviors. The drying kinetics and the shrinkage approach are finally combined with the global energy balance for a single slice, in order to describe the evolution of surface temperature and other yacón slice properties along the drying period. Graphical abstract: Image 1 Highlights: The evolution of yacón slices under convective drying was studied at pilot scale. 81. Experimental data were collected under controlled air temperature and humidity. 79. Moisture loss observations were approximated through a novel two-parameter model. 81. Shrinkage of yacón slices was described by a combination of hypothetical models. 80. The global energy balance allowed to predict surface water activity and temperature. 84.